2014
DOI: 10.3892/mmr.2014.2740
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture inhibits apoptosis of splenic lymphocytes in traumatized rats through modulation of the TNF-α/NF-κB signaling pathway

Abstract: Surgical trauma leads to a severe deterioration of the immune system. Electroacupuncture (EA) may improve the immunodeficiency that occurs following surgery; however, the underlying signaling mechanisms require further study. In the present study, 40 rats were equally randomized into four groups: Control; Control + EA; Trauma; Trauma + EA. EA was applied at the 'Zusanli' (ST36) and 'Lanwei' (Extra37) acupoints, immediately following surgery. The splenic T cells were isolated from the rats 24 h after surgery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…NF-κB can be activated by the phosphorylation of a tyrosine residue of the p50 subunit which then translocates into the nucleus after the release of IκB, and is known to be crucial factor in the differentiation of neuronal cells [ 114 , 115 ]. As NF-κB is known to be a downstream regulator of tumor necrosis factor (TNF)-α, it is particularly important in the neuroinflammatory processes involved in depression [ 116 ]. Given its major role in mediating inflammatory processes, many researchers have suggested that NF-κB is not only present in various immune cells but also on the surface of the BBB [ 117 ].…”
Section: Epo-induced Intracellular Signaling Pathwaysmentioning
confidence: 99%
“…NF-κB can be activated by the phosphorylation of a tyrosine residue of the p50 subunit which then translocates into the nucleus after the release of IκB, and is known to be crucial factor in the differentiation of neuronal cells [ 114 , 115 ]. As NF-κB is known to be a downstream regulator of tumor necrosis factor (TNF)-α, it is particularly important in the neuroinflammatory processes involved in depression [ 116 ]. Given its major role in mediating inflammatory processes, many researchers have suggested that NF-κB is not only present in various immune cells but also on the surface of the BBB [ 117 ].…”
Section: Epo-induced Intracellular Signaling Pathwaysmentioning
confidence: 99%
“…NF-κB is a key transcription factor of stress and injury in eukaryotic cells, which is involved in normal activities and disease processes of the body, involving growth and development, cell differentiation, apoptosis, immune response, inflammatory response, trauma, stress Inflammation, tumor growth, chronic inflammatory diseases and other processes [ 16 , 17 ]. NF-κB can be activated by a variety of stimuli, it is the central regulator of innate immunity and acquired immunity, it can regulate the expression of various pro-inflammatory factors and anti-apoptotic proteins[ 16 ], and its nuclear translocation appears in normal animals Daily rhythm, the transcriptional activity of NF-κB is inhibited by increasing endogenous corticosterone under mild stress [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a key transcription factor of stress and injury in eukaryotic cells, which is involved in normal activities and disease processes of the body, involving growth and development, cell differentiation, apoptosis, immune response, inflammatory response, trauma, stress Inflammation, tumor growth, chronic inflammatory diseases and other processes [ 16 , 17 ]. NF-κB can be activated by a variety of stimuli, it is the central regulator of innate immunity and acquired immunity, it can regulate the expression of various pro-inflammatory factors and anti-apoptotic proteins[ 16 ], and its nuclear translocation appears in normal animals Daily rhythm, the transcriptional activity of NF-κB is inhibited by increasing endogenous corticosterone under mild stress [ 17 ]. Current research shows that glucocorticoid induces NF-κB gene transcription in two ways, one is through protein–protein interaction, in the nucleus, glucocorticoid-glucocorticoid receptor complex and NF- κB active p65 subunit of κB interacts and prevents the binding of transcriptionally active NF-κB and DNA recognition structures in the promoter region of the gene of interest.…”
Section: Discussionmentioning
confidence: 99%